TRAINING INTCOM (INTERPERSONAL COMMUNICATION) MENINGKATKAN PRODUKTIVITAS ORGANISASI HIMPUNAN MAHASISWA - Rahmah, Dian Dwi Nur; Zahra, Nirita; Teluma, Theresia Roselyn Amabilis Sarbiti; Affifa, Ken; Aldisa, Olga Olivia; Oktavia, Nia Ariesma Nur (LPPM Institut Pendidikan Nusantara Global, 2024)
Communication has a very strategic place in the management of an organization. One measure of the good and bad of the organization depends on the quality of communication. Interpersonal communication as a link between communicator and communicant, is considered to be the most effective communication to change one's attitude, opinion, or behavior. The purpose of this training is to understand the concept of interpersonal communication and improve interpersonal communication skills between members to create effective performance in the organization. The method used in this training program is experiential learning which is carried out face-to-face to members of the Himpunan Mahasiswa Kedokteran Gigi Mulawarman University. The results of the training showed that there was an increase in understanding of interpersonal communication after being given training. This is evidenced based on the pre-test and post-test treatment with interpersonal communication training, the t-count result is -4.996 (< t table = 1.688) with p = 0.000 (p> 0.05) which means that there is a difference in the level of understanding of interpersonal communication in the Himpunan Mahasiswa Kedokteran Gigi Mulawarman University before and after being given treatment, namely with interpersonal communication training, and an increase in understanding by 10.6 percent. The Chairperson of the Dentistry Student Association provides feedback that members are more active in expressing opinions and can carry out interpersonal communication properly to improve the performance of the Himpunan Mahasiswa Kedokteran Gigi.